A Simple Measure of the Intensity of Capital Controls - Warnock, Francis (IMF Working Papers; Working Paper ;, 2001)
We present a readily available monthly measure of the intensity of capital controls across 29 emerging market countries that is based on the degree of restrictions on foreign ownership of equities. The initial opening of a market as given by our measure corresponds well with the liberalization dates of Bekaert and Harvey (2000a). In addition, our measure provides information on the extent of the initial opening as well as the evolution of the liberalization over time. After presenting the measure, we compare it to other existing measures of capital controls and briefly describe empirical applications concerning home bias, capital flows to emerging markets, and the effects of financial liberalization on the cost of capital.